Prior self-control exertion and perceptions of pain during a physically demanding task. (November 2017) - Boat, Ruth; Taylor, Ian M.
Abstract: Objectives: Exertion of self-control has been associated with impaired performance on subsequent physical tasks also requiring self-control, but it remains unknown why this occurs. This study, therefore, explored whether a) prior self-control exertion reduces subsequent persistence on a physically demanding task, and b) whether any observed performance decrements could be explained by changes in perceptions of pain. Method: In a within-subject design, sixty-three individuals completed an easy (congruent) Stroop task or a difficult (incongruent) Stroop task that required self-control. Participants were then required to remain in a physically demanding posture (i.e., a 'wall-sit') until voluntary exhaustion and their perception of pain was recorded during the task. Results: When participants completed the difficult Stroop task, they quit the wall-sit sooner. This decrement in performance was explained by greater perceptions of pain at the beginning of the wall-sit. Conclusions: Perceptions of pain may, therefore, be an important attentional mechanism explaining why self-control use interferes with subsequent persistence during physically effortful tasks. Highlights: Exertion of self-control significantly reduced subsequent physical performance. Individuals had elevated perceptions of pain during the early stages of the task. Perceptions of pain may explain why self-control use interferes with performance.